Strategi Live Streaming, Content Marketing, dan Online Customer Reviews untuk Mengoptimalkan Keputusan Pembelian Konsumen - Fera Valentina; Sutianingsih Sutianingsih; Agustin Diah Nurbaiti; Prisella Putri Octaviyani (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
In the contemporary digital era, marketing methods have undergone significant changes along with the increasing use of online technology. In this case, live streaming, content marketing, and online customer reviews have become more important components in business marketing strategies aimed at influencing consumer decisions. This study aims to explore the ways in which these three factors influence customer decisions. The study results show how big an impact live streaming, content marketing, and online customer reviews have on purchasing decisions. Studies show that a company's ability to influence consumer decisions increases with how well the company integrates content marketing with live streaming, and online customer reviews have a significant influence. These findings show how important it is for companies to monitor and manage these variables to influence more consumer decisions in the digital era.